2021
DOI: 10.1287/orsc.2020.1402
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Ambiguous Offerings

Abstract: This paper studies how audience members categorize and evaluate ambiguous offerings. Depending on whether audience members categorize ambiguous offerings based on prototypes or goals, they activate two distinct cognitive mechanisms and evaluate differently ambiguous offerings. We expect that when audiences engage in goal- versus prototype-based categorization, their evaluation of ambiguous products increases. We theorize that, under goal-based categorization, the perceived utility of unclear attributes increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…Third, the Empathy and Simplicity frames proved superior to Goal framing, itself commanding a weakly greater, but insignificant impact on take‐up than the base treatment condition ( Charity treatment—see Table 3). That Goal frame triggered a slightly more positive reaction than the prototypical Charity frame is congruent with recent research that found that goal‐based categorization provides more positive evaluations in ambiguous contexts (e.g., Barsalou, 1991; Boulongne & Durand, 2021). Still, the Goal frame alone failed to drastically raise take‐up (relative to Charity frame)—its effectiveness was surpassed by the Simplicity and Empathy frames.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Third, the Empathy and Simplicity frames proved superior to Goal framing, itself commanding a weakly greater, but insignificant impact on take‐up than the base treatment condition ( Charity treatment—see Table 3). That Goal frame triggered a slightly more positive reaction than the prototypical Charity frame is congruent with recent research that found that goal‐based categorization provides more positive evaluations in ambiguous contexts (e.g., Barsalou, 1991; Boulongne & Durand, 2021). Still, the Goal frame alone failed to drastically raise take‐up (relative to Charity frame)—its effectiveness was surpassed by the Simplicity and Empathy frames.…”
Section: Discussionsupporting
confidence: 89%
“…The frame emphasizes goal congruence, that is, the fit between the goals of the target beneficiaries and those of Program P. When a beneficiary perceives goal congruence, she is more motivated to engage with Program P (Barsalou, 1991; Vancouver & Schmitt, 1991), leading to higher take‐up rates. Relatedly, goal‐based categorization has been shown to generate positive behavioral attitudes toward products when communication includes information about unusual cues (Barlow, Verhaal, & Angus, 2019; Boulongne & Durand, 2021). As such, the Goal frame is a natural candidate to contrast with the typical Charity communication frame used as our base treatment group and traditionally employed in CSI communication.…”
Section: Setting and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that audiences can categorize a product according to their needs and goals (Barsalou, 1983; Durand & Paolella, 2013). Therefore, even an ambiguous product can receive a relatively positive evaluation if it serves certain functions and fulfills the goals of consumers (Boulongne & Durand, 2021). Taking the furniture industry as an example, although furniture produced by different manufacturers has distinct design styles (e.g., modern, country, traditional, etc.…”
Section: Within‐ and Between‐organization Distinctiveness Of Product ...mentioning
confidence: 99%
“…Strategy scholars have emphasized how differentiation helps organizations establish competitive advantages and reduce competition (Barney, 1991; Hoopes, Madsen, & Walker, 2003; Porter, 1987), while institutional theorists have stressed how conformity enables organizations to achieve legitimacy and avoid penalties caused by deviance in behavior (DiMaggio & Powell, 1983; Durand & Kremp, 2016; Zucker, 1977). In response, a robust body of work has emerged in strategy and organization research around the notion of “optimal distinctiveness” (OD), which focuses on identifying the optimal level of distinctiveness that positively shapes stakeholder perceptions and enhances performance (Boulongne & Durand, 2021; Haans, 2019; Navis & Glynn, 2011; Semadeni, 2006; Zhao, Fisher, Lounsbury, & Miller, 2017; Zuckerman, 2016). To date, most OD research has focused on the organizational level by examining what constitutes an optimal level of distinctiveness of an organization as compared to its peers in terms of organizational level attributes such as strategies (Deephouse, 1999; McNamara, Deephouse, & Luce, 2003), innovation activities (Jennings, Jennings, & Greenwood, 2009; Roberts & Amit, 2003), business models (Zott & Amit, 2007), and organizational narratives (Haans, 2019; Taeuscher, Bouncken, & Pesch, 2021).…”
Section: Introductionmentioning
confidence: 99%